2005
DOI: 10.1021/jp053208l
|View full text |Cite
|
Sign up to set email alerts
|

Through the Channel and around the Channel:  Validating and Comparing Microscopic Approaches for the Evaluation of Free Energy Profiles for Ion Penetration through Ion Channels

Abstract: Microscopic calculations of free energy profiles for ion transport through biological ion channels presents a very serious challenge to modern simulation approaches. The main problem is due to the major convergence problems associated with the heterogeneous landscape of the electrostatic environment in ion channels and with the need to evaluate the profile associated with the transfer of the ion from bulk water to the channel environment. This problem is compounded by the lack of reliable and relevant benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 51 publications
(78 reference statements)
1
80
0
Order By: Relevance
“…We view these PMFs Figure 5 and the calculated changes in the total reorganization energies (∆∆λ). The correlation coefficient (R 2 ) for the linear regression is 0.8062. as preliminary results due to the well-known convergence problems associated with evaluation of PMF for large displacements (51). Thus we consider the work function as the free energy needed to bring the donor acceptor distance from either the minimum or the point with lowest energy (in the range of up to 4 Å) to 3 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We view these PMFs Figure 5 and the calculated changes in the total reorganization energies (∆∆λ). The correlation coefficient (R 2 ) for the linear regression is 0.8062. as preliminary results due to the well-known convergence problems associated with evaluation of PMF for large displacements (51). Thus we consider the work function as the free energy needed to bring the donor acceptor distance from either the minimum or the point with lowest energy (in the range of up to 4 Å) to 3 Å.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of charge-transfer reaction, the PMF that uses only the solute coordinates involves significant hysteresis (see ref 51) while approaches that emphasize the charging coordinates (by using a mapping potential that changes the solute charges) are more reliable. Furthermore, as emphasized in our previous studies (e.g., refs 49 and 50), the EVB approaches capture the contribution of nonequilibrium effects to the barrier.…”
Section: Methodsmentioning
confidence: 99%
“…Using m and the FEP/ US approach, we sort the system in two dimensions (X 1 ) R g ; X 2 ) rmsd) rather than in one dimension as in ref 38.…”
Section: Exploring the Changes In The Folding Landscapementioning
confidence: 99%
“…However, the PMF approach does not quantify absolute solvation energies of ligand, which makes it difficult to detect potential problems in treatment of long-range effect and boundary conditions (7,8). A comparison of PMF and FEP in ion channel study indicated the former suffered more seriously from hysteresis (9). Alternatives to free-energy pathway calculations include linear response analysis (LRA) (10) and linear interaction energy (LIE) (11), where only the ligand-bound and unbound states are simulated.…”
mentioning
confidence: 99%